Extension of the Periods for Consent to and Payment of Quota Increases. (Policy Papers; Policy Paper ;, 2016)
This paper proposes a further six-month extension of the period for members to consent to an increase in their quotas under the Fourteenth General Review of Quotas ('Fourteenth Review') through June 30, 2017. The current deadline is due to expire on December 30, 2016. However, Board of Governors Resolution No. 66-2 provides that the Executive Board may extend the period for consent as it may determine. An extension under Resolution No. 66-2 will also extend the periods of consent for quota increases under the 2008 Reform of Quota and Voice (Resolution No. 63-2) and the Eleventh General Review of Quotas (Resolution No. 53-2). This paper also proposes a further six-month extension of the period for payment of quota increases under the Fourteenth Review, and an extension for the payment of the quota increases under the 2008 Reform, through June 30, 2017.